Development, Validation, and Practicality of a Wordwall-Based Educational Game for Senior High School Acid-Base Learning - Bunga Artika Sari; Elvy Rahmi Mawarnis; Dwivelia Aftika Sari (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aimed to develop and evaluate the validity and practicality of a Wordwall-based educational game for senior high school acid-base learning. The study employed a Research and Development (R&D) design using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The developed media integrated game-based quizzes, instant feedback, visual elements, and concept-based challenges to support joyful learning and deepen students’ conceptual understanding of acid-base material. Data were collected through expert validation sheets, student response questionnaires, and a teacher interview. The product was validated by three expert validators and evaluated by one chemistry teacher. The implementation stage involved 29 students from class XI.F.1 and 31 students from class XI.F.2 at SMAN 10 Sijunjung. The validation results showed that the material aspect obtained a validity score of 80%, the language aspect obtained 75%, and the media design aspect obtained 95%, categorized as valid to highly valid. Student responses indicated that the media was very practical, with practicality scores of 86,75% in class XI.F.1 and 88,00% in class XI.F.2 in terms of ease of use, attractiveness, usefulness, and time efficiency. Teacher feedback also indicated that the media helped present acid-base concepts in a more interactive and engaging way. The findings indicate that the Wordwall-based educational game is feasible and practical for use as an alternative digital learning medium in acid-base instruction. Further research is recommended to examine its effectiveness on students’ conceptual understanding, learning motivation, and learning outcomes.